Rumen Anaerobic Fungi of Cattle and Sheep - Bauchop, T. (1979)
Plant fragments obtained from natural rumen digesta of fistulated cattle and sheep were examined by scanning electron microscopy. Various plant materials suspended in the rumen for different times were examined likewise. By 2 h large numbers of phycomycetous fungal zoospores were found attached to fibrous plant fragments, particularly vascular tissues. The subsequent development of these fungi resulted in production of thalli with extensive rhizoids and with sporangia up to 175 μm long. Scanning electron microscope examination of plant fragments randomly selected from natural rumen contents of both cattle and sheep demonstrated widespread colonization by large populations of these anaerobic fungi. Furthermore, all plant fragments suspended in nylon bags in the rumen were also extensively colonized. These findings demonstrate that plant fragments in the rumen are the sites of colonization and development by the anaerobic phycomycetous fungi. In addition, the results suggest that these fungi may form a significant part of the rumen microbiota in cattle and sheep fed on fibrous diets and suggest that they may be important in fiber digestion.